2019
DOI: 10.1177/1524838019867156
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence in Saudi Arabia: A Systematic Review

Abstract: Intimate partner violence (IPV) is a serious public health issue at the global level, with cultural differences in its nature and prevalence. Most of the current evidence related to IPV comes from Western countries; however, there is a lack of evidence of IPV in developing countries such as Saudi Arabia. The issue of IPV has been investigated in Saudi Arabia only recently, and data have been inconsistent and inconclusive. Hence, we conducted a systematic review of the extant literature devoted to IPV prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…Characteristics of included systematic reviews and meta-analyses are shown in Table 2 . Only two reviews included global data [ 22 , 23 ], most of which were limited to a country or a group of countries, mainly from Asia [ 4 , 23 , 24 , 25 , 26 , 27 , 28 ] and Africa [ 4 , 26 , 27 , 29 , 30 ], followed by America [ 31 , 32 ], Europe [ 32 ], and Australia [ 32 ]. The number of studies included in the reviews giving information about IPV prevalence during pregnancy ranged from 2 [ 24 ] to 73 [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics of included systematic reviews and meta-analyses are shown in Table 2 . Only two reviews included global data [ 22 , 23 ], most of which were limited to a country or a group of countries, mainly from Asia [ 4 , 23 , 24 , 25 , 26 , 27 , 28 ] and Africa [ 4 , 26 , 27 , 29 , 30 ], followed by America [ 31 , 32 ], Europe [ 32 ], and Australia [ 32 ]. The number of studies included in the reviews giving information about IPV prevalence during pregnancy ranged from 2 [ 24 ] to 73 [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies included in the selected reviews were cross-over studies, in which there was only a single evaluation of the women sometime during pregnancy. Some of the reviews also included cohort studies [ 4 , 24 , 25 , 30 , 31 , 32 ]. Reviews included studies giving information about IPV only at pregnancy [ 22 , 23 , 24 , 27 , 29 , 30 ], both during pregnancy or at postpartum [ 4 , 30 , 31 , 32 ], during pregnancy, or having a child 2 years old or younger [ 25 ] or at current pregnancy or any pregnancy [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations